A Case of an Omentum Inflammatory Myofibroblastic Tumor with Intraabdominal Bleeding - Matsuda, Masakazu; Arima, Nobuyuki; Shimada, Shinya; Tajima, Rumiko; Baba, Kenichiro; Yokoyama, Sachio; Furuhashi, Satoshi; Uemura, Shinichiro (Nippon Shokaki Geka Gakkai zasshi, 2007)
A 47-year-old man admitted in April 2006 for upper abdominal pain was found in laboratory data to have an elevated white blood cell count of 15, 200/mm3 and CRP of 22.63mg/dl. Abdominal computed tomography indicated a nonenhanced intraabdominal tumor connected to the stomach wall and ascites assumed to be blood. After inflammation decreased, we conducted distal gastrectomy for the tumor, which was located on the gastric wall and connected widely to the greater curvature of the antrum. Histopathologically, the tumor was hyperplasia of spindle cells with lymphocyte and plasma cell infiltration. Immunohistrogically, however, spindle cells were positive for vimentin, smooth muscle actin, and desmin indicating myofibroblasts. From these findings, we made a difinitive diagnosis of a rare omental inflammatory myofibroblastic tumor.